Saharan Dust Deposition in Central Europe in 2016—A Representative Year of the Increased North African Dust Removal Over the Last Decade - Rostási, Ágnes; Topa, Boglárka Anna; Gresina, Fruzsina; Weiszburg, Tamás G.; Gelencsér, András; Varga, György (Frontiers in Earth Science, 2022)
Changes in circulation patterns associated with climate change have led to an increase in the frequency and intensity of Saharan dust events (SDEs) in the Carpathian Basin. The annual number of dust events was 4.2 on average between 1979 and 2010, while in the period of 2011–2018, it has increased to 10.3. This study presents a quantitative assessment of wet deposition of dust particles to Lake Balaton (Central Europe) with mineralogical and particle size distribution measurements. In addition to a comprehensive, systematic SDE identification process, rainwater samples were collected in 2016, and the particles on the filters were characterised using a range of analytical techniques. The atmospheric transport of particulates and moisture was evaluated using HYSPLIT Lagrangian trajectory model. XRD measurements revealed that during these events, the major minerals were quartz, kaolinite and 10-Å phyllosilicates. In addition, mineralogical source markers of arid dust (palygorskite and smectite) were also identified in majority of the analysed samples. Based on the results, wet deposition fluxes of dust particles were estimated for the region. 2016 was a typical and representative year for the decade, with twelve identified dust episodes. The synoptic patterns of the events fit well with the typical meteorological character of the North African dust intrusions with enhanced atmospheric meridionality described earlier. From the twelve episodes of 2016, seven were depositional events when wet deposition could be observed at ground level. Dust material of five episodes was analysed in detail, while particles of the two February wet deposition episodes were only granulometrically characterised. General uncertainties that hinder the characterisation of mineral dust in climate models were also observed in the granulometric and dust flux data of the sampled material. The particle size of the deposited dust was coarser than the upper cut-off level of grain size of the models. In addition, the discrepancies between measured and simulated deposition values clearly demonstrated the incorrect representation of dust flux in numerical simulations (partly due to inaccurate grain size data in the models).